Hospitalizations Due to Adverse Drug Events in the Elderly—A Retrospective Register Study - Laatikainen, Outi; Sneck, Sami; Bloigu, Risto; Lahtinen, Minna; Lauri, Timo; Turpeinen, Miia (Frontiers in Pharmacology, 2016)
Adverse drug events (ADEs) are more likely to affect geriatric patients due to physiological changes occurring with aging. Even though this is an internationally recognized problem, similar research data in Finland is still lacking. The aim of this study was to determine the number of geriatric medication-related hospitalizations in the Finnish patient population and to discover the potential means of recognizing patients particularly at risk of ADEs. The study was conducted retrospectively from the 2014 emergency department patient records in Oulu University Hospital. A total number of 290 admissions were screened for ADEs, adverse drug reactions (ADRs) and drug-drug interactions (DDIs) by a multi-disciplinary research team. Customized Naranjo scale was used as a control method. All admissions were categorized into ‘probable’, ‘possible’, or ‘doubtful’ by both assessment methods. In total, 23.1% of admissions were categorized as ‘probably’ or ‘possibly’ medication-related. Vertigo, falling, and fractures formed the largest group of ADEs. The most common ADEs were related to medicines from N class of the ATC-code system. Age, sex, residence, or specialty did not increase the risk for medication-related admission significantly (min p= 0.077). Polypharmacy was, however, found to increase the risk (OR 3,3; 95% CI, 1.5-6.9 p = 0.01). In conclusion, screening patients for specific demographics or symptoms would not significantly improve the recognition of ADEs. In addition, as ADE detection today is largely based on voluntary reporting systems and retrospective manual tracking of errors, it is evident that more effective methods for ADE detection are needed in the future.